2015
DOI: 10.2106/jbjs.n.00540
|View full text |Cite
|
Sign up to set email alerts
|

Porous Tantalum Metaphyseal Cones for Severe Tibial Bone Loss in Revision Knee Arthroplasty

Abstract: Porous tantalum tibial cones offer a promising management option for severe tibial bone loss. At the intermediate-term follow-up (five to nine years), porous tantalum tibial cones had durable clinical results and radiographic fixation. The biologic ingrowth of these implants offers the potential for successful long-term structural support in complex knee reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 39 publications
7
127
0
8
Order By: Relevance
“…There was radiographic component incorporation in all patients in their studies. As more longterm reports [10] become available, such techniques may prove to be good options for improved fixation in patients with morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There was radiographic component incorporation in all patients in their studies. As more longterm reports [10] become available, such techniques may prove to be good options for improved fixation in patients with morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Lachiewicz et al [19] experienced no failures at 39-month followup in their cohort of 27 knees. In larger series, Kamath et al [16] reported [ 95% survivorship at an average 70-month followup, whereas Graichen et al [12] found 89% survivorship in 193 sleeves at a mean 42-month followup. The results of our study are comparable to the best published results with the use of femoral head allografts.…”
Section: Resultsmentioning
confidence: 98%
“…Alexander [6], Huang et al [15], Agarwal et al [1], and Graichen and colleagues [12] reported statistically significant improvements in the KSS, Oxford, and WOMAC scores at an average of 2 to 4 years postsurgery in patients treated using trabecular metal cones. Kamath et al [16] reported a KSS score of 80 points (representing a sustained improvement of 25 points) at a minimum 5-year followup with the use of trabecular metal cones. This report is from a designer surgeon series; however, it does represent one of the longest published series with the use of trabecular metal cones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations